Effectiveness of an Evidence-Based Amputee Rehabilitation Program: A Pilot Randomized Controlled Trial. Issue 5 (17th January 2020) - Gailey, Robert; Gaunaurd, Ignacio; Raya, Michele; Kirk-Sanchez, Neva; Prieto-Sanchez, Luz M; Roach, Kathryn
Abstract: Background: Despite the prevalence of lower limb amputation (LLA), only a small percentage of people with LLA actually receive physical therapy post amputation and are rehabilitated to their full potential level of function. There is a need for the development of a rehabilitation program that targets impairments and limitations specific to people with LLA. Objective: The objective of this study was to determine whether the Evidence-Based Amputee Rehabilitation program would improve functional mobility of people with unilateral transtibial amputation (TTA) who have already completed physical therapy and prosthetic training. Design: This study was a randomized, wait-list control, single-blinded pilot clinical trial. Setting: This study researched participants who had received postamputation rehabilitation to varying degrees, either in an inpatient and/or outpatient settings. Participants: The participants in this study included veterans and nonveterans with unilateral TTA due to dysvascular disease and trauma. Intervention: This study included a prescription-based rehabilitation program for people with amputations. Measurements: Results were measured with The Amputee Mobility Predictor with (AMPPro) and without a prosthesis (AMPnoPro) and 6-Minute Walk Test (6MWT) at baseline and at the end of the 8-week intervention. Results: The intervention group improved on the AMPPro scores (36.4 to 41.7), AMPnoro scores (23.2 to 27.1), and 6MWT distance (313.6 to 387.7 m). The effect size for the intervention was very large (1.32). In contrast, the wait-list control group demonstrated no change in AMPPro scores (35.3 to 35.6), AMPnoPro scores (24.7 to 25.0), and 6MWT distance (262.6 m to 268.8 m). Limitations: The sample size was small. A total 326 potential candidates were screened with 306 unable to meet inclusion criteria or unwilling to participate. Conclusion: People with unilateral TTA who received Evidence-Based Amputee Rehabilitation program demonstrated significant improvement in functional mobility, with most participants (66.7%) improved at least 1 K-level (58.3%) and greater than the minimal detectable change (66.7%).